Tsunami Potential Due To Strike-Slip Earthquake Affected by Submarine Landslide - Wiko Setyonegoro (Marine Geological Institute of Indonesia, 2016)
The most of earthquakes in the western part of North of Sumatra, Indonesia have tsunami potential. This paper discuss about tsunami height which was triggered by large energy of earthquake along strike-slip fault and submarine landslide. Beyond of a view historical tsunamis in the western part Sumatra in Aceh, which was occured on April 11, 2012 have given several questions for the majority of earth scientist in relation with the potential for tsunami. The 8.6 M earthquake might have no tsunami potential significantly, with the hypothesis that mechanism of the earthquake source is strike-slip. However BMKG, in accordance with standard operating procedures stated that this earthquake